Ice Class Requirements on Side Shell Structures - A comparison of local strength class requirements regarding plastic design of ice-reinforced side shell structures - Bergbom Wallin, Filip; Åkerström, Carl-Johan (Chalmers tekniska högskola / Institutionen för sjöfart och marin teknik, 2012)
The demand for shipping in Arctic regions is increasing, and with this comes an increased interest in ice-strengthened ships. Today there exist several class rules satisfying additional requirements for operation in geographical areas with ice-infested waters. Hence, it is crucial for classification societies, designers and ship-owners to understand how formulations of each rule-set impact on structural members to be able to design a ship that suits a certain operational purpose. The aim of this thesis is to perform a comparison study on structural properties and steel grades on mid-bodies with a constant cross section, regarding ice-strengthening requirements relevant in the icereinforced region. To provide an overview of fundamental differences of ice class rule-sets, a comparison is conducted through case studies in which three different fictitious ships are used. The rule formulations of Det Norske Veritas (DNV), Finnish-Swedish Ice Class Rules (FSICR), IACS Polar Class and the Russian Maritime Register of Shipping (RS) are compared with an emphasis on the local structure and material requirements. Since the comparison is focused on rule-sets, no numerical analysis on the strength is considered. To enable comparisons between class rules, a computer code is developed where the rule-sets are adopted. The computer code uses ship particulars together with rule formulations to calculate the outcome on the actual local strength of each rule-set. Main parameters, i.e. frame spacing, direction of frames, displacement and yield strength in the rule formulation are varied in order to find their influence on the weight and structural properties. In addition to this, issues in the results are identified together with recommendations of areas that need to be further looked into with a numerical analysis on the actual structure. The comparison shows that the direction of framing plays a major role in the reinforcements needed and the total weight outcome on mid-bodies with a constant cross section. Due to the shape of the ...